Antinematodal activity of some Malaysian plant extracts against the pine wood nematode, Bursaphelenchus xylophilus - Mackeen, M.M.; Ali, A.M.; Abdullah, M.A.; Nasir, R.M.; Mat, N.B.; Razak, A.R.; Kawazu, K. (John Wiley & Sons, 1997)
Methanolic extracts of 79 Malaysian plants representing 42 families were assessed for antinematodal activity against Bursaphelenchus xylophilus using a fungal-feeding assay. Extracts of 27 plants from 19 families showed antinematodal activity, while 52 species were inactive. Five extracts (Sauropus androgynus, Eugenia polyantha, Areca catechu, Piper betle and Piper nigrum) exhibited very strong activity against Bursaphelenchus xylophilus at a minimum effective dose (MED) of 0.625 mg per ball. Strong antinematodal activity (MED: 1.25-2.5 mg per ball) was shown by the extracts of Spondias cyntherea, Codiageum variegatum, Euodia glabra and Cicca acida. Eleven extracts (Carica papaya, Ipomoea aquatica, Ocimum basilicum, Leea gigantea, Pithecellobium jiringa, Crypteronia paniculata, Myristica fragrans, Murraya koenigii, Leucaena leucocephala, Melastoma malabathricum and Morinda citrifolia) demonstrated moderate activity between MED of 5 and 10 mg per ball, and weak activity was observed in seven extracts (Ipomoea batatas, Cymbopogon citratus, Garcinia atroviridis, Psophocarpus tetragonolobus, Tamarindus indica, Allium odorum and Stenochalaena palustris).